Cultura tributaria en trabajadores de la empresa, Centro Comercial Monarca, Iquitos - año 2021 - Vasquez Lazo, Yuridia (2023)
The present research work entitled "Level of Tax Culture in Company Workers, Monarca Shopping Center, Iquitos - year 2021, was carried out with the objective of determining what is the level of Tax Culture in the workers of the Monarca Shopping Center company, year 2022, for which a descriptive type of research was chosen, of a non-experimental design, where 49 company workers who voluntarily decided to participate in this research work were taken as the study population, to whom it was applied the survey technique and the questionnaire as an instrument; According to the analysis of the results, it was determined that the workers of the company Centro Commercial Monarca, year - 2022, have a medium level of Tax Culture and it is concluded that the workers also have a medium level of knowledge and tax awareness.